Perspectives of young people and their parents in the transition of cochlear implant services: Implications for improved service delivery. (January 2014) - Olds, Janet; Fitzpatrick, Elizabeth M; Séguin, Christiane; Moran, Linda; Whittingham, JoAnne; Schramm, David
Abstract : Objectives: Youth and young adults with cochlear implants are now transitioning from pediatric to adult services in increasing numbers. Research in other areas of health care has indicated that there is a gap in the transition from pediatric services for the young adult, and that it is important to obtain their perspectives to reduce disruption and improve care. Previous research has documented issues from the perspective of cochlear implant professionals. The objectives of this study were to examine current practices from the perspective of young adults and their families and to make recommendations for future practice. Methods: Interviews were conducted with 11 individuals, including cochlear implant recipients and their parents. All patients were within 4 years of transition between pediatric and adult hospital services: four youths were pediatric patients, and two had been discharged to adult services. Qualitative research methodology was used to identify key themes. Results: All participants indicated that they had not anticipated a change to an adult hospital as part of their plan of care. Key themes from interviews were differences between pediatric and adult hospitals, challenges in establishing new relationships with professionals, specific concerns about new health care settings and procedures, and the need for youth to develop independent health-related skills in the context of parental involvement. Discussion: Themes identified through interviews with young people with cochlear implants and their parents were similar to research in other areas of health care, as well as to themes identified in focus groups with professionals providing cochlear implant services. There were some differences which highlight both needs in the provision of health care and opportunities for providers and patients to collaborate to provide improved service delivery.